Muscular and cardiorespiratory parameters of Brazilian professional futsal players: comparison between top national and regional level athletes - Gabriela B. David; Cristine L. Alberton; Maria Laura R. Brizio; Victor S. Coswig; Laura G. Jung; Jennifer R. Silveira; Felipe F. Reichert (Motriz: Revista de Educacao Fisica, 2022)
Abstract Aim: To compare muscular and cardiorespiratory parameters between Brazilian professional futsal athletes from different competitive levels (national versus regional). A secondary aim was to explore the correlation of physical fitness variables between both competitive levels. Methods: Twenty-two futsal players (24.7 ± 3.7 years), 11 from a regional team and 11 from a national team, were evaluated with countermovement jump test (lower limbs muscle power), square test (the speed with change direction), RSSA (anaerobic power), and YOYOIR1 (aerobic power). Tests were performed in the middle of the season for both teams. Results: The speed with change direction (p = 0.001) and mean anaerobic power (p = 0.04) were higher for national than the regional players. Sprint performance decreased similarly for national and regional level players (p < 0.001), but the latter had poorer performance (p = 0.044). From the fourth sprint on, sprints for the national level players were slower than the first three, while for the regional level players, each sprint speed was slower than the subsequent. A significant correlation was found between anaerobic power with jump height (r = −0.50; p = 0.01), speed with change direction (r=0.65; p = 0.001) and distance covered in the YOYOIR1 (r = −0.54; p = 0.01). Conclusion: National-level athletes were more agile and presented a higher mean anaerobic power than regional ones. Moreover, national-level athletes presented better performance along with repeated sprint tests, maintaining this performance for a longer time during the test.